Effects of organic amendment on soil organic carbon in treated soft clay in paddy cultivation area - Muhammad Rendana,; Wan Mohd Razi Idris,; Sahibin Abdul Rahim,; Zulfahmi Ali Rahman,; Tukimat Lihan,; Habibah Jamil, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Soft clay soil has become a major problem in paddy cultivation area. Nearly half of the total paddy field in Kedah State, Malaysia cannot be utilized for paddy cultivation because of soft clay soil. The problem is related to the presence of weak hardpan structure that permits the soil to experience continuous wet condition. The soil also causes in the alteration of many processes soil organic carbon sequestration and turnover, but the main effect on the land is decrease in soil fertility. To investigate the effects of soft clay soil on soil organic carbon content, stock and change rate, the trial has been conducted in Alor Senibong paddy field area in Kedah, Malaysia examining the problematic paddy field that associated with soft clay soil problem. Hasil Tani Organic Compound (HTOC) was an organic soil amendment that used to enhance soil organic carbon in this study. Paddy field with the presence of soft clay soil showed a low soil organic carbon content and stock around 0.67% and 1.01 t·ha-1, respectively (depth 0-15 cm). The reduction of soil organic carbon content in soft clay soil was likely because of the waterlogged soil environment, the stability of soil aggregates and decline in humification process which then reduced soil organic carbon input. After being treated with HTOC, soil organic carbon content and carbon stock in soft clay soil have significantly increased by 0.67-3.14% and 1.01-4.76 t·ha-1 (depth 0-15 cm), respectively, yielding a mean monthly carbon change rate of 4.36 g C kg−1·mth.−1 (depth 0-15 cm). As whole, the succession of HTOC application to improve soil organic carbon content in this study could be employed in other paddy field areas that associated with soft clay soil problem.